Stabilitas Parameter Kualitas 35 Klon Teh Sinensis (Camellia Sinensis var. Sinensis) Yang Diolah Menjadi Teh Hijau Dengan Metode Panning dan Steaming - Prayoga, M. Khais; Syahrian, Heri; Rahadi, Vitria Puspitasari; Maulana, Hilman; Shabri, Shabri; Akhdya, Alina; Martono, Budi; Santoso, Tri Joko; Utami, Dwinita Wikan (Universitas Bangka Belitung, 2023)
The Research Institute for Tea and Cinchona (RITC) has a collection of 35 tea clones of the Sinensis type whose performance parameters for green tea are unknown, so it is necessary to screen these clones as an effort to characterize the performance parameters for green tea quality. The purpose of this study was to determine the clones with stable quality parameter performance in two processing methods namely panning and steaming as well as the suitability of each clone with the processing method. The diversity of green tea quality parameter performance was analyzed using principal component analysis (PCA). The stability of the green tea quality parameters was tested using the Finaly-Wilkinson method, while the differences in the performance of the green tea quality parameters in the panning and steaming methods were analyzed using combined variance followed by an additional Honest Significant Difference (BNJ) test at the 5% level. The results of this study were clones I.1.101, I.2.34, I.2.85, II.1.3, II.1.60, R1, S2, GMBS 3, and GMBS 4 which had stable green tea quality in two processing methods, namely panning and steaming. . Meanwhile clones I.2.34, I.4.113, II.2.146, II.3.16, R3, S1, S3, and GMBS 3 will show good quality green tea when processed using the panning method, while clones I.1.93, II.2.108 , II.4.32, II.4.178, SGMBA, and Yabukita will show good quality green tea when processed using the steaming method.